Environments favorable to healthy lifestyles: A systematic review of initiatives in Canada - Tegwen Gadais; Maude Boulanger; François Trudeau; Marie-Claude Rivard (Elsevier, 2018)
Background: In recent years, a number of initiatives aimed at promoting healthy lifestyles in health-friendly environments have been implemented. The purpose of this review is to synthesize initiatives conducted in Canada and documented in publications for the period 1995-2015 in order to gain a better understanding of their objectives and impacts. Methods: A systematic review of Canadian initiatives published over the past 20 years was conducted from multiple databases (i.e., Scopus, SPORTDiscus, PubMed, Academic search complete, Reseausante.com, Cairn, and Erudit). In total, 264 publications were identified and retained for the final analysis based on 5 criteria: (1) publication between 1995 and 2015, (2) online availability, (3) research conducted in Canada, (4) main topic related to environments favorable to healthy lifestyles (EFHL), and (5) publication in French or English. Results: A sharp increase in the number of studies on EFHL was observed between 2010 and 2015 (57%). Two major lifestyle components-physical activity and nutrition-and 2 environmental aspects-neighborhood and built environment-were the elements most frequently examined regarding adults (48%), young people (34%), and seniors (9%), using quantitative (60%) and qualitative (18%) methods. Furthermore, the analysis reveals a greater focus on the municipal (53%) than the national or provincial levels (31%). Conclusion: This work is a first map of Canadian studies related to EFHL. It clarifies the definition of EFHL and classifies its components. As well, it documents the issues raised, the research methods employed, and the role of stakeholders, while outlining a new research agenda that includes dimensions of EFHL formerly neglected by researchers, namely, political and sociocultural spheres of action.